International law : cases and materials with Australian perspectives - Rothwell, Donald R (Cambridge University Press, 2018)
The nature of international law -- Sources of international law -- Law of treaties -- International and municipal law -- International legal personality -- Sovereignty over territory -- Jurisdiction -- State responsibility -- Human rights -- Law of the sea -- International environmental law -- International trade law -- Use of force -- Enforcement of international law -- The peaceful settlement of international disputes.